Humor Content and Media Credibility: An Analysis of Audience Engagement on the Instagram Account @simamaungcom - Ramzy Fauza Setiawan; Martha Tri Lestari (CHANNEL: Jurnal Komunikasi, 2025)
Humor is a powerful communication tool that goes beyond entertainment to build emotional connection, ease tension, and increase message effectiveness. In today’s digital era, it has become a strategic means of capturing attention, shaping perceptions, and sustaining engagement across social media platforms. This study examines the role of humorous content in enhancing audience engagement and strengthening media credibility on the Instagram account @simamaungcom, an independent platform focused on the Persib Bandung supporter community. Using qualitative content analysis of 24 humorous posts uploaded between January and March 2025, the findings indicate that humor significantly increases interaction and meets the audience’s affective, social, and cognitive needs, consistent with the Uses and Gratifications Theory. Two primary forms of humor, identification and clarification, contribute to humanizing communication, simplifying complex football-related information, and reinforcing solidarity within the Bobotoh community. In the context of high social media use and a strong culture of humor among supporters, these results demonstrate that humor functions not only as an entertainment medium but also as an element that supports collective identity formation, sustains emotional closeness, and reduces tension during periods of poor team performance. These findings offer valuable insights for digital media practitioners in designing effective humor strategies to enhance engagement, strengthen audience relations, and uphold credibility within the dynamic environment of sports communication.